2013
DOI: 10.7600/jpfsm.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness, physical activity, exercise training and cognitive function in older adults

Abstract: Cognitive impairment is a major health and social issue. Over the past decade many studies have reported that engaging in physical activity and exercise training, and a higher level of physical fitness, can postpone the onset of age-associated cognitive decline or reduce its impact. In this review, therefore, we focused on the association between physical fitness, physical activity, exercise training and cognitive function in older adults. It is assumed that physical fitness, including cardiorespiratory fitnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Intervention strategies for improving either muscle strength, cognitive functioning, or both may improve the health aspects of these outcomes. A review article by Okura et al [77] suggests that cardiorespiratory fitness interventions, especially in combination with other healthy behaviors, may help to reduce the risk of cognitive impairment. Martin et al [78] completed a systematic review of cognitive-based interventions for healthy older persons and persons with cognitive impairment, and suggested that cognitive interventions may lead to performance gains but such effects may not be attributed to the cognitive training directly.…”
Section: Interventions For Muscle Strength and Cognitive Functionmentioning
confidence: 99%
“…Intervention strategies for improving either muscle strength, cognitive functioning, or both may improve the health aspects of these outcomes. A review article by Okura et al [77] suggests that cardiorespiratory fitness interventions, especially in combination with other healthy behaviors, may help to reduce the risk of cognitive impairment. Martin et al [78] completed a systematic review of cognitive-based interventions for healthy older persons and persons with cognitive impairment, and suggested that cognitive interventions may lead to performance gains but such effects may not be attributed to the cognitive training directly.…”
Section: Interventions For Muscle Strength and Cognitive Functionmentioning
confidence: 99%
“…Even though some functions decline with aging, the ability to make decisions and take actions is guided by the life experience and knowledge that has been accumulated as people get older [ 48 , 49 ]. Although physical changes that accompany aging occur in everyone, the decline in cognitive function can be delayed by physical exercise [ 50 ]. Lifestyles from a young age also affect our health.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this intervention program is adopting multiple exercises effective for cognitive function 38,39) , for example, SSE, resistance training, and dual task training. Furthermore, because mental state is an important factor in dementia prevention 40) , this program includes recreation to improve participant mental state (depression and self-efficacy).…”
Section: Summary Of the Exercise Class For Improving Cognitive And Phmentioning
confidence: 99%